(untitled) (Indonesian Tourism Justice Review, 2025)
Tourism is one of the main drivers of economic growth in Indonesia, particularly in coastal regions, yet it poses significant environmental risks that threaten long-term sustainability. This paper explores the environmental impacts of tourism in Indonesia’s coastal areas, including coral reef degradation, marine pollution, and coastal erosion, which are exacerbated by climate change. Focusing on popular tourist destinations like Bali, Lombok, and Komodo, the study investigates how tourism-related activities, such as mass resort construction, water sports, and waste disposal, contribute to environmental degradation. Drawing on environmental justice theories, the paper argues that tourism’s environmental toll disproportionately affects low-income coastal communities who rely on natural resources for their livelihoods. The paper evaluates existing policies aimed at mitigating these impacts and identifies gaps in enforcement and regulation. It proposes sustainable tourism practices that incorporate climate change adaptation strategies, stricter environmental regulations, and community engagement in conservation efforts. Ultimately, the study emphasizes the need for an integrated approach to tourism development that balances economic growth with environmental protection and social equity.